The Role of Extratropical Air–Sea Interaction in the Autumn Subseasonal Variability of the North Atlantic Oscillation - Nie, Yu; Ren, Hong-Li; Zhang, Yang (Journal of climate, 2019)
Considerable progress has been made in understanding the internal eddy–mean flow feedback in the subseasonal variability of the North Atlantic Oscillation (NAO) during winter. Using daily atmospheric and oceanic reanalysis data, this study highlights the role of extratropical air–sea interaction in the NAO variability during autumn when the daily sea surface temperature (SST) variability is more active and eddy–mean flow interactions are still relevant. Our analysis shows that a horseshoe-like SST tripolar pattern in the North Atlantic Ocean, marked by a cold anomaly in the Gulf Stream and two warm anomalies to the south of the Gulf Stream and off the western coast of northern Europe, can induce a quasi-barotropic NAO-like atmospheric response through eddy-mediated processes. An initial southwest–northeast tripolar geopotential anomaly in the North Atlantic forces this horseshoe-like SST anomaly tripole. Then the SST anomalies, through surface heat flux exchange, alter the spatial patterns of the lower-tropospheric temperature and thus baroclinicity anomalies, which are manifested as the midlatitude baroclinicity shifted poleward and reduced baroclinicity poleward of 70°N. In response to such changes of the lower-level baroclinicity, anomalous synoptic eddy generation, eddy kinetic energy, and eddy momentum forcing in the midlatitudes all shift poleward. Meanwhile, the 10–30-day low-frequency anticyclonic wave activities in the high latitudes decrease significantly. We illustrate that both the latitudinal displacement of midlatitude synoptic eddy activities and intensity variation of high-latitude low-frequency wave activities contribute to inducing the NAO-like anomalies.